2021
DOI: 10.29337/ijsp.139
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Various Surgical Procedures Addressing Long Head of Biceps Pathology: Protocol for a Systematic Review and Meta-Analysis

Abstract: Introduction:The long head of biceps tendon is a common source of anterior shoulder pain and impaired function. Multiple surgical procedures are available as treatment options, but the optimal procedure is not known. The aim of this systematic review and meta-analysis is to review the literature to assess the clinical effectiveness of various surgical procedures to treat pain arising from the long head of biceps. Methods:The study protocol was designed and registered prospectively on PROSPERO (International pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… 21 A protocol for the study was registered with International Prospective Register for Systematic Reviews ( https://www.crd.york.ac.uk/prospero/ ), and published prior to study commencement. 22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 A protocol for the study was registered with International Prospective Register for Systematic Reviews ( https://www.crd.york.ac.uk/prospero/ ), and published prior to study commencement. 22 …”
Section: Methodsmentioning
confidence: 99%
“…This study is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement 21. A protocol for the study was registered with International Prospective Register for Systematic Reviews (https://www.crd.york.ac.uk/prospero/), and published prior to study commencement 22…”
Section: Methodsmentioning
confidence: 99%